BIOMIMETIC AND ANTIOXIDANT ACTIVITY OF NANOCRYSTALLINE CERIUM DIOXIDE - Tsekhmistrenko, O.S.; Tsekhmistrenko, S.I.; Бітюцький, В.С.; Oleshko, O.A. (World of Medicine and Biology, 2018)
The conducted analysis of scientific literature shows the widespread application in biology and medicine of nano compounds of cerium dioxide that exhibit biomimetic and antioxidant activity. High biocompatibility degree, low toxicity and catalytic activity of nanodispersed cerium dioxide allows us to consider it as a promising nanobio material for biomedical applications. The role of nanocrystalline cerium dioxide in protecting cells from oxidative stress is characterized. Oxygen non-stoichiometry, associated with it ability to participate in oxidative-reduction processes in a living cell, as well as the ability to auto regeneration ensure high efficiency of nanodispersed cerium dioxide using. Cerium (Ce) is a rare-earth element that belongs to lanthanides. The uniqueness of Cerium is due to the fact that it can exist in different oxidation states (Ce3+ and Ce4+), unlike most other rare earth metals, which are predominantly in trivalent state. Cerium itself has no biological significance in the physiology of mammals, but Ce3+ soluble salts are traditionally used for biomedical purposes because of their bacteriostatic, bactericidal, immunomodulatory, and antitumor activity. The biological activity of cerium dioxide nanoparticles is determined by its oxygen non-stoichiometry, which depends on the size of the nanoparticle and the surface ligand. High degree of biocompatibility, low toxicity and catalytic activity of nanodispersed cerium dioxide allow it to be considered as a promising nanomaterial for biomedical applications. However, today all the possible mechanisms of its biological activity are poorly understood.It has been shown that nanoseria can act as a mimetic of superoxide dismutase, catalase, some oxidase, oxidoreductase and phosphatase, and it is also able to participate in the neutralization of active forms of nitrogen.Nanocerium acts as a mimetic of superoxide dismutase (SOD) and catalase, and its efficiency in the neutralization of radicals is proportional to the concentration of Ce3+ ions on the surface of the particle.SOD-like activity of NDC is comparable to that of natural enzyme. In the case of superoxide anion dismutration, the formation of hydrogen peroxide and transitional compound - cerium Ce(ООН)(OH)3 hydroperoxide on the surface of nanodispersed cerium dioxide.NDC is able to inactivate a highly active hydroxyl radical. The presence of cerium dioxide nanoparticles reduces the concentration of OH∙. Numerous studies have shown that SeO2 nanoparticles effectively protect cells against the effects of hydrogen peroxide and other peroxides. The catalase activity can be changed by modifying cerium dioxide nanoparticles with various metal ions.The compounds of nanodispersed cerium dioxide exhibit oxidase properties. In this case, the pH-dependent peroxidase-like activity is established. It has been established that the size and surface ligands affect the reactivity of nano dispersed cerium dioxide. The possibility of repeated use of SeO2 nanoparticles as an antioxidant was revealed.NDC is able to inactivate active forms of nitrogen and nitrogen-containing free radicals. The ability of cerium dioxide nanoparticles to inactivate peroxynitrile (ONOO-) is shown, which causes damage to a number of biomolecules by adsorption of the surface of carbonate ions. New data on the catalytic activity of nanodispersed cerium dioxide prove its similarity to phosphatase. CeO2 is able to catalyze the hydrolysis of organic phosphate ester. The ability of cerium dioxide nanoparticles to decompose fighting poisonous substances has been revealed.Thus, it is possible to adjust its antioxidant and prooxidant properties and enzyme activityby changing the stoichiometry of the nanodispersed cerium dioxide. There is a need for further research on the functions, properties and role of NDC in order to improve the integration of biomimetic nanomaterials into the human body and animals, which is the basis for new scientific developments in the field of biology, chemistry, medicine for the prevention, diagnosis and treatment of various diseases.
Keywords: nano-particles; cerium dioxide; mimetics; oxidative stress; superoxide dismutase